Artificial intelligence‐enhanced skin‐like sensors based on flexible nanogenerators. Issue 5 (8th October 2022) - Wang, Yiqian; Tan, Puchuan; Wu, Yuxiang; Luo, Dan; Li, Zhou
Abstract: Artificial intelligence‐enhanced skin‐like sensors based on flexible nanogenerators have been widely used in physiological signal acquisition, artificial organ, sensory simulation, human movement status recognition, and other biomedical related fields due to their excellent biocompatibility, comfortable wearing experience, high sensing accuracy, and low power consumption. In this paper, the working principle, evolution process, and several established general strategies of artificial intelligence‐enhanced skin‐like sensors are summarized in detail. More importantly, this paper further reviews several recent important advances on artificial intelligence enhanced skin‐like sensor, and systematically analyzes and compares these works according to their principles and application directions. In the discussion section, we also list the current concerns of stress adaptation, stretchability–conductivity, algorithm optimization, function integration, and propose potential solutions to these problems. We hope that the deep integration of artificial intelligence and flexible nanogenerators can bring more enlightenment to the progress of biomedical engineering in the future. Abstract : In this paper, the working principle, evolution process, and several established general strategies of artificial intelligence‐enhanced skin‐like sensors are summarized in detail. More importantly, this paper further reviews several recent important advances on artificial intelligence‐enhanced skin‐like sensor, and systematically analyzes and compares these works according to their principles and application directions.